2018
DOI: 10.1088/1361-6463/aab97e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multifunctional piezoelectric metastructures for low-frequency bandgap formation and energy harvesting

Abstract: Vibration-based energy harvesting is a growing field for generating low-power electricity to use in wireless electronic devices, such as the sensor networks used in structural health monitoring applications. Locally resonant metastructures, which are structures that comprise locally resonant metamaterial components, enable bandgap formation at wavelengths much longer than the lattice size, for critical applications such as low-frequency vibration attenuation in flexible structures. This work aims to bridge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 50 publications
0
55
0
3
Order By: Relevance
“…Piezoelectric energy harvesting is driven by the deformation of the host structure due to mechanical or acoustic vibrations that convert to an electrical potential via embedded piezoelectric materials. To increase harvester efficiency, using ideas based around structuring surfaces, several approaches such as creating a parabolic acoustic mirror, point defects in periodic phononic crystals and acoustic funnels have been employed [28][29][30][31]; lenses to concentrate narrow band vibrations have been proposed using phononic crystals [32][33][34], ideas based around localised defect states [35], and resonant metamaterials endowed with piezoelectric inserts have appeared very recently [36]. Our aim here is to complement these studies by using a graded array to create a metawedge [37], and introduce piezoelectric elements into the array, this addresses one of the main challenges in energy harvesting which is to achieve broadband energy production from ambient vibration spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric energy harvesting is driven by the deformation of the host structure due to mechanical or acoustic vibrations that convert to an electrical potential via embedded piezoelectric materials. To increase harvester efficiency, using ideas based around structuring surfaces, several approaches such as creating a parabolic acoustic mirror, point defects in periodic phononic crystals and acoustic funnels have been employed [28][29][30][31]; lenses to concentrate narrow band vibrations have been proposed using phononic crystals [32][33][34], ideas based around localised defect states [35], and resonant metamaterials endowed with piezoelectric inserts have appeared very recently [36]. Our aim here is to complement these studies by using a graded array to create a metawedge [37], and introduce piezoelectric elements into the array, this addresses one of the main challenges in energy harvesting which is to achieve broadband energy production from ambient vibration spectra.…”
Section: Introductionmentioning
confidence: 99%
“…This can affect the overall power density of the system as well as the circuit interface, which becomes more complex with respect to single-mode harvesters. Conversely, it is worthwhile to appreciate that multimodal schemes can be well integrated with metamaterial concepts, leading to truly multifunctional designs [82] with enhanced energy-harvesting capabilities.…”
Section: Topological Rainbow Trapping For Elastic Energy Harvestingmentioning
confidence: 99%
“…Resonant metamaterial components facilitate band gap formation for long wavelength approximation, which is useful for vibration attenuation. Based on this, Sugino and Erturk (2018) proposed multifunctional piezoelectric metastructures for low-frequency band gap formation and energy harvesting. They concluded that energy can be harvested from locally resonant metastructures without significantly affecting vibration attenuation in the locally resonant band gaps.…”
Section: Introductionmentioning
confidence: 99%